The Role of Probiotic in Reducing Hepatic Inflammation Among NAFLD Patients: an Evidence-Based Case Report - Alvin Nursalim; Ummi Ulfah Madina; Cosmas Rinaldi A Lesmana (Acta Medica Indonesiana)
Aim: to know the effectiveness of probiotic in reducing hepatic inflammation among non-alcoholic fatty liver disease (NAFLD) patients. Methods: we performed literature searching regarding the potential role of probiotic in reducing hepatic inflammation among NAFLD patients. Results: six articles were finally critically appraised. All six studies had good validity and importance. These studies unanimously reported that probiotic is useful in reducing hepatic inflammation, and liver fat content. However, further evidence is needed to show whether or not probiotic is beneficial reducing cirrhosis progression and liver-related mortality. Conclusion: probiotic owns robust potential to treat NAFLD. Probiotic reduce hepatic inflammation, as shown by the reduction of liver aminotransferase, and inflammatory markers. Based on this evidence based report, probiotic is a promising adjunct therapy for NAFLD.